Capacity of Civil Service Police and Fire Department in Controlling Street Vendors in Sukabumi City - Andika Zelin Aji Santoso; Andi Mulyadi; Yana Fajar FY Basori (Utan Kayu Publishing, 2025)
This study analyzes the capacity of the Satuan Polisi Pamong Praja (Satpol PP) and Pemadam kebakaran (Damkar) of Sukabumi City in enforcing regulations Pedagang Kaki Lima (PKL) trading in prohibited areas, as stipulated in Sukabumi City Regional Regulation No. 10 of 2013, Pasal 21. Employing a qualitative descriptive approach, data were gathered through interviews with officials (Cikole, Diskumindag), PKL, residents of R. Syamsudin SH Street, observations, and documentation. Policy capacity was measured using five dimensions from Horton et al. (2003): human resources, infrastructure-technology-financial resources, strategic leadership, program management and implementation processes, and collaboration networks. Findings reveal limitations in human resources (personnel shortages, multifunctional rotations, short operational hours); outdated infrastructure (aging vehicles, limited CCTV, reliance on e-lapor); adaptive strategic leadership via daily briefings and school socialization despite flexible relocations; phased management (persuasion, tiered warnings, UMKM coaching); and inter-agency networks (with Dishub, Police, sub-districts) requiring enhanced joint sweeps in high-risk zones like Ahmad Yani and seven prohibited streets. Key challenges include vendor resistance (high relocation costs), banner damage, budget constraints, and low e-lapor awareness. Recommendations emphasize training enhancements, infrastructure renewal, consistent evaluation cycles, monthly meetings, and digital socialization for sustainable enforcement.